Effect of Diode Laser (805) nm on alpha-toxin production and antibioticsensitivity of Staphylococcus aureus - Ismail, Munira; Waleed, Sinai; Jabbar, Faheema; Ibrahim, Khawla (Iraqi Journal of Science, 2024)
The effect of low level laser radiation on Staphylococcus aureus with differentexposure times has been studied. Thirty skin samples [swabs] were collected frompatients with burn and wound infections of Al-yarmouk teaching hospital, during theperiod from November 2010 to March 2011. Ten isolates of S. aureus were identified bytheir cultural characteristics, microscopic examination, and biochemical tests. The tenisolates were exposed to diode laser [805nm] at different exposure times [1min., 3min.and 5min.]. The activity of bacteria to produce alpha toxin and its sensitivity toantibiotics were determined before and after irradiation. The result of alpha toxinproduction of ten irradiated isolates were illustrated that toxin production was decreasesafter different time of exposure [1, 3 and 5 min.] of irradiation. The effect of diode laseron the sensitivity of S. aureus to antibiotics discs shows slightly increase in the diameterof inhibition zone to these antibiotics at different time of exposure.